'The enchanted garden': a changing image in children's literature - Beck, Catherine (2003)
This study is a historico-cultural examination of the role of the garden in literature written for children between 1850 and 2000. The garden is considered from two perspectives - as a setting for children's play, and as a cultural symbol that changes over time to reflect social concerns. The central assumption of this thesis is that the garden may be considered as a symbol of childhood itself. My main concern is to investigate the nature of the construct of childhood as evidenced in texts written at different periods, focussing on what it might have meant to be a child at those times. In doing so, I frequently have cause to contrast these definitions of ‘childhood’ with each other, and with contemporary ones. The notion of the garden suggests to me a series of ‘structural oppositions’ (Rose, 1984), such as innocence/experience, civilisation/nature, home/away, enclosure/exposure; all of which are typical concerns of literature in general, and, arguably, particularly significant themes in children's literature and thus pertinent to its study. I suggest that the garden as a common setting for children's literature also acts as a meeting-place, or compromise, for some of these pairings. Since children are generally subject to adults, I consider that some of these oppositions can be regarded in terms of power and control. The thesis emphasises the ‘constructedness’ of such oppositions, in order to demonstrate the mythological - and often adult-serving - nature of much thinking about childhood. I explore texts as diverse as Barrie's Peter Pan (1911) and Pullman's His Dark Materials (1995-2000) in order to illustrate changes in the mythology of childhood, and in the deployment of the icon of the child in the garden. The study concludes with a detailed exploration of Pearce's Tom's Midnight Garden (1958), which I believe expresses many symbolic meanings of the garden image in a particularly convincing way, with considerable artistic and emotional integrity.